Description of Characteristics and Level of Knowledge About Personal Hygiene During Menstruation - Bonita Dwi Juniana Bahari; Sri Hartutik (Universitas Muhammadiyah Palu, 2023)
Background: The majority of young women have some wrong beliefs and habits associated with Personal Hygine during of menstruation. Prevalence in Central Java about reproductive health is less at 68.6%. One of the main problems of adolescent reproductive health in Indonesia is due to the lack of information about reproductive health. The impact that occurs when adolescents know less about Personal hygiene during menstruation, that is, it causes susceptible to reproductive infections. Objective: Knowing an overview of the level of knowledge of grade VII young women about Personal hygiene during menstruation at SMP N 1 Karanganyar. Method: This study is quantitative discriptive. The number of respondents studied was 63 respondents. The level of knowledge is measured using a questionnaire instrument. Result: The results showed that the level of knowledge of class VII adolescent respondents about personal hygiene during menstruation at SMP Negeri 1 Karanganyar was good as many as 58 respondents (92.2%), while the remaining 5 respondents with sufficient category (7.9%) with the majority aged 13 years as many as 42 respondents (66.7%) and obtained information sources from parents as many as 28 respondents (44.4%). Conclusion: The level of knowledge of grade VII young women about Personal hygiene during menstruation at SMP Negeri 1 Karanganyar is good.